The psychology of nightmares (horror) in the cinematic movie (Al-Academy, 2022)
Psychology is one of the sciences that consciously overlap in terms of mutual influence with art forms in general and cinematic arts in particular. The psychological effect can be extrapolated into the visual image through the characters and their actions, especially the adoption of psychoanalytic ideas and proposals that came by (Freud), The cinema benefited from the concepts of psychology and participated in the process of creativity and the manufacture of events or the actions of characters, such as the concepts of consciousness and subconsciousness to express the psychological dimension of the film events, these data can be counted on the level of nightmares in the cinematic movies.The methodological framework included the research problem, which is determined by the following question: What is the psychology of nightmares (horror) in the cinematic movie? And then the researcher stated the value of the research, as well as the aims and limits of the research. The theoretical framework included two sections, the first section: the psychology of the dream. As for the second section: the nightmares (horror) in the cinematic movie, and the researcher came up with the indicators of the theoretical framework. As for the research procedures, it includes the research methodology, the research tool, the research community, the unit of analysis and the research sample. Finally, the analysis of the intended sample represented by the movie (The Call of the Beast), and the researcher came out with a set of results from the analysis of the research sample and conclusions